Análisis de riesgos laborales de los puestos de trabajo e implementación de mejoras de la empresa Montajes Industriales González - Díaz Quishpe, Katherine Fernanda (2017)
This thesis project is to obtain the title Industrial Production and Safety Technology aims to analyze the work risk of the jobs of the company Montages Industrials González, to minimize the existing risks and in this way protect the safety of the employee. This project is divided into five chapters. The first describes the company, the problems encountered and the objectives to be realized. The second chapter describes the risk factors that exist in any activity that takes place within the company. The third chapter details the analysis of current occupational risks in each of the company's jobs and in this way elaborates the risk matrix according to GTC45. The fourth chapter describes the measures necessary to control the occupational hazards encountered. With the implementation of these, the company will help reduce risks, its workers will carry out their activities safely, and their facilities will have the minimum safety requirements and will have a training manual for their workers. In the fifth chapter are the conclusions that were obtained when implementing the proposed safety improvements in each job and the recommendations that are made so that the occupational hazards are the minimum when performing a job.